"Without Contraries Is No Progression": William Blake’s Monistic Understanding of Theodicy as Reflected in His Engravings of the Book of Job - Evans, Annette (Journal for semitics, 2023)
In the book of Job, Job is initially described as "perfect and upright," yet Yahweh allows Satan to inflict terrible suffering on him. From their Deuteronomistic orientation, Job’s comforters insist that Job must have sinned and deserves punishment. If Job is truly innocent, the quandary of theodicy arises because Yahwistic monism views Yahweh as the one and only loving, all powerful God of justice and mercy. However, in his exegesis in his set of engravings of the book, the nineteenth-century poet and artist William Blake viewed Job not as "perfect and upright," but as wrapped in a self-absorbed bubble of false piety, dedicated to traditional memory and habit. This article selects six of Blake’s engravings and by means of a literary-psychological methodological approach demonstrates how Blake anticipated certain modern exegetical methods in his aim to "justify the ways of God to man." He claimed the right to use his own imaginative response to the text, rather than rely on the meaning handed down by tradition and memory. The initial divide between heaven and earth is bridged when the youthful Elihu rejects their traditional wisdom, and brings Job to the point where he can experience God as an immanent divine presence. The advance of science, for instance, Darwin’s theory of the origin of the species, and subsequent research in a variety of disciplines has resulted in a new understanding of the inevitability of suffering and evil, and goes some way to validate Blake’s monistic insistence that "without contraries is no progression."